PENERAPAN DIGITAL MOVING AVERAGE FILTER PADA SKIN SENSOR INFANT WARMER UNTUK MENGUKUR SUHU - Kuspranoto, Abdul Haris; Ulin Nuha ABA, Muhammad (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2024)
Accurate and stable measurement of a baby's body temperature is a critical element in neonatal care, especially for premature babies or babies with medical conditions that require intensive attention. Currently, skin sensors integrated with infant warmers are a common solution for continuously monitoring baby's body temperature. However, temperature fluctuations and environmental noise can interfere with measurement accuracy. This research aims to increase the accuracy of temperature measurements using the Digital Moving Average Filter (DMAF) on the skin sensor in the infant warmer. DMAF is applied to reduce noise and fluctuations, thereby producing more stable and accurate temperature data. This method was tested using a dataset of temperature measurements from newborn babies. The results show a significant improvement in temperature measurement accuracy of up to 97.94%, with a substantial reduction in fluctuations and noise. In addition, temperature fluctuations do not exceed 1 degree Celsius after using the DMAF method. Thus, the application of DMAF to skin sensor infant warmers provides clear benefits in improving the quality of neonatal care by providing more precise and responsive temperature control, as well as reducing the risk of dangerous medical conditions due to temperature instability. These findings provide a strong foundation for further development in sensor technology and temperature regulation in infant warmers, with great potential to improve the safety and well-being of newborns.